An Open Source Multimodal Image-Guided Prostate Biopsy Framework - Shah, Amit; Zettinig, Oliver; Maurer, Tobias; Precup, Cristina; Schulte Zu Berge, Christian; Weiss, Jakob; Frisch, Benjamin; Navab, Nassir (Springer Verlag, 2014)
Although variousmodalities are used in prostate cancer imaging, transrectal ultrasound (TRUS) guided biopsy remains the gold standard for diagnosis. However, TRUS suffers from low sensitivity, leading to an elevated rate of false negative results. Magnetic Resonance Imaging (MRI) on the other hand provides currently the most accurate imagebased evaluation of the prostate. Thus, TRUS/MRI fusion image-guided biopsy has evolved to be the method of choice to circumvent the limitations of TRUS-only biopsy. Most commercial frameworks that offer such a solution rely on rigid TRUS/MRI fusion and rarely use additional information from other modalities such as Positron Emission Tomography (PET). Other frameworks require long interaction times and are complex to integrate with the clinical workflow. Available solutions are not fully able to meet the clinical requirements of speed and high precision at low cost simultaneously.We introduce an open source fusion biopsy framework that is low cost, simple to use and has minimal overhead in clinical workflow. Hence, it is ideal as a research platform for the implementation and rapid bench to bedside translation of new image registration and visualization approaches. We present the current status of the framework that uses pre-interventional PET and MRI rigidly registered with 3D TRUS for prostate biopsy guidance and discuss results from first clinical cases.
CRIS-Team Scopus Importer:2023-03-08
Keywords: MRI; Multimodal image-guided biopsy; Open source software; PET; Prostate cancer; TRUS